2018
DOI: 10.1186/s13550-018-0436-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of [123I]FP-CIT SPECT scans on the novel brain-dedicated InSPira HD SPECT system: a head-to-head comparison

Abstract: The InSPira HD system, a novel brain-dedicated SPECT scanner, allows for imaging with a high spatial resolution. Here, we tested whether this scanner can be used to image the dopamine transporter adequately. Therefore, striatal phantom and patient data acquired on the InSPira were compared head-to-head with the well-validated brain-dedicated NeuroFocus system. A striatal phantom filled with [123I] and 14 subjects (after [123I]FP-CIT injection) were scanned on both systems. [123I]FP-CIT SPECT scans were visuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Finally, to be able to study a large population, we included subjects from multiple studies that were performed on two different scanners. However, as we have previously demonstrated that striatal ratios are closely correlated between both cameras [ 37 ], and lean subjects and subjects with obesity were equally distributed between both cameras, it is unlikely that a difference between both cameras has significantly affected our findings.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Finally, to be able to study a large population, we included subjects from multiple studies that were performed on two different scanners. However, as we have previously demonstrated that striatal ratios are closely correlated between both cameras [ 37 ], and lean subjects and subjects with obesity were equally distributed between both cameras, it is unlikely that a difference between both cameras has significantly affected our findings.…”
Section: Discussionmentioning
confidence: 74%
“…SPECT imaging was performed on one of two brain-dedicated cameras: (i) the InSPira HD system (Neurologica, Boston, MA, USA), acquisition time per slice 180 s, slice thickness 4 mm; or (ii) the 12-detector, single-slice brain-dedicated scanner (Neurofocus 810; Strichman Medical Equipment, Cleveland, OH, USA), acquisition time per slice 210 s, slice thickness 5 mm. SPECT images were corrected for attenuation, and reconstructed as previously described [ 37 , 38 ]. We have previously demonstrated that striatal ratios are closely correlated between both cameras [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has to be noticed that all our testing and training data originates from general purpose SPECT cameras. Images from dedicated brain scanners, like the InSPira HD SPECT system [23], might lead to diagnoses that are based on detailed local diminished uptake, as can be seen with such highresolution systems. Preliminary results (data not shown) of our model using a test set of DaTSCAN images acquired on the InSPira HD SPECT system indeed showed that the model did not generalize well enough for data from a dedicated brain scanner.…”
Section: Discussionmentioning
confidence: 99%
“…The patient received a dopamine transporter SPECT scan of the brain according to a standard protocol that has been described in detail in Chap. 5 and previously [1]. In short, the patient was injected with 120 MBq [ 123 I]FP-CIT (GE Healthcare) and scanned 3 h post-injection on a brain-dedicated SPECT scanner (InSPira).…”
Section: Dopamine Transporter Spect Scanmentioning
confidence: 99%